2020
DOI: 10.2147/ott.s250028
|View full text |Cite
|
Sign up to set email alerts
|

<p>ZNRD1-AS1 Promotes Nasopharyngeal Carcinoma Cell Invasion and Metastasis by Regulating the miR-335–ROCK1 Axis</p>

Abstract: Background: Long noncoding RNAs (lncRNAs) are known as key regulators in many cancer types, but their biological functions in nasopharyngeal carcinoma (NPC) remain largely unknown. In the present study, we aim to explore the role of the lncRNA ZNRD1-AS1 in NPC tumor development. Methods: The role of ZNRD1-AS1 in NPC tissues and cells was explored by using quantitative real-time PCR assay. Cellular behavioral experiments were used in testing NPC cell proliferation, invasion, and migration. Luciferase reporter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…For example, LINC00152 drive ANXA2-mediated invasion and metastasis of NPC cells via sponging miR-613 [19]. Another lncRNA ZNRD1-AS1, up-regulated in NPC and associated with advanced TNM stages, was also reported increased the NPC cell invasiveness and metastasis via affecting miR-335-ROCK1 axis [21]. In some other cancers, Wang and colleagues showed that the EPB41L4A-AS2-miR-301a-5p-FOXL1 axis inhibits hepatocellular carcinoma development [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, LINC00152 drive ANXA2-mediated invasion and metastasis of NPC cells via sponging miR-613 [19]. Another lncRNA ZNRD1-AS1, up-regulated in NPC and associated with advanced TNM stages, was also reported increased the NPC cell invasiveness and metastasis via affecting miR-335-ROCK1 axis [21]. In some other cancers, Wang and colleagues showed that the EPB41L4A-AS2-miR-301a-5p-FOXL1 axis inhibits hepatocellular carcinoma development [39].…”
Section: Discussionmentioning
confidence: 99%
“… 24 In nasopharyngeal carcinoma, miR-335 inhibits invasion and metastasis of cancer cells by directly regulating ROCK1. 72 Besides, miR-335 inhibits GC cell migration and invasion via regulating ROCK1. 58 MiR-335 acts as a tumor suppressor to modulate cell migration and invasion by the down-regulation of ROCK1 in HCC.…”
Section: Biological Role Of Mir-335 In Various Cancersmentioning
confidence: 99%
“… [ 58 ] LncRNA NEAT1 HCC [ 82 ] LncRNA ZEB1-AS1 Gastric cancer. [ 42 ] LncRNA DANCR Osteosarcoma [ 59 ] LncRNA DANCR Cervical cancer [ 56 ] LncRNA SLCO4A1-AS1 Bladder cancer [ 48 ] LncRNA CASC9 NSCLC [ 29 ] LncRNA LINC01510 Thyroid carcinoma [ 65 ] LncRNA TINCR Ovarian cancer [ 113 ] LncRNA XIST NSCLC [ 64 ] LncRNA XIST Bladder cancer [ 110 ] lncRNA ZNRD1-AS1 Nasopharyngeal Carcinoma [ 72 ] CircRNA Circ-EIF4G3 Gastric cancer [ 70 ] Circ_103973 Cervical Cancer [ …”
Section: Factors Modulating Mir-335 In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…FTH1P3 enhances the proliferation, migration and invasion of oral squamous cell carcinoma and laryngeal squamous cell carcinoma [ 29 , 30 ]. Zinc ribbon domain containing 1 antisense 1 ( ZNRD1-AS1 ) accelerates invasion and metastasis of NPC cells [ 31 ]. Besides, pseudogenes contribute to HNSCC progression in vivo [ 32 ].…”
Section: Introductionmentioning
confidence: 99%